2018
DOI: 10.14569/ijacsa.2018.091034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Distance Measures for Feature based Image Registration using AlexNet

Abstract: Image registration is a classic problem of computer vision with several applications across areas like defence, remote sensing, medicine etc. Feature based image registration methods traditionally used hand-crafted feature extraction algorithms, which detect key points in an image and describe them using a region around the point. Such features are matched using a threshold either on distances or ratio of distances computed between the feature descriptors. Evolution of deep learning, in particular convolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Наступний модуль системи -це модуль пошуку, який відповідає за зіставлення ключових векторів вхідного фрагменту відео із тими, що вже знаходяться в базі. Процес, що містить визначення подібності [7], використовує такі основні концепції:…”
Section: порівняння кадрівunclassified
See 1 more Smart Citation
“…Наступний модуль системи -це модуль пошуку, який відповідає за зіставлення ключових векторів вхідного фрагменту відео із тими, що вже знаходяться в базі. Процес, що містить визначення подібності [7], використовує такі основні концепції:…”
Section: порівняння кадрівunclassified
“…Вибір ефективної функції подібності векторів базується на дослідженні [7], де розглянуто низку популярних методів та порівняння метрик експериментальних застосувань. Причому вхідними векторами для порівняння є результат останнього незв'язного шару згорткової нейронної мережі, що є ідентичним способом і в запропонованій системі.…”
Section: порівняння кадрівunclassified
“…The Inria Holidays and Oxford Buildings datasets were used for their experiments, which revealed that the fusion feature could contribute to the improvement of image retrieval. Besides those works that we discussed above, there are many AlexNet's applications in extracting features for hand gestures, remote sensing images, image registration and bearing fault diagnosis as well [33], [34], [36]- [38].…”
Section: Feature Extractionmentioning
confidence: 99%
“…The action units [5], [6] of the face are the fundamental unit of the expression which contain sensitive information of expression. Convolutional neural network (CNN) consist of convolutional layer, pooling layer and fully connected network [7] is the most interesting tool and technology that, produces promising result [8] for any high-level scientific computation [9], [10]. Convolutional neural networks are not only for facial emotion recognition that we applied in the under described research, but also in several classifications such as human disease classification [11], [12], and plant disease classification [13].…”
Section: Introductionmentioning
confidence: 99%